Sistem Penjadwalan Ruangan Berbasis Website dengan Validasi Benturan Jadwal - Salma Nurul Ikhsani; Nova Tri Romadloni (TIN: Terapan Informatika Nusantara, 2026)
The utilization of information technology holds a vital position in elevating the excellence of data management and services in government agencies. This research was conducted at the Samber Nyawa Information Center of the Karanganyar Regency Communication and Information Service, which continues to face challenges in managing room utilization. The problem is that the current room scheduling procedure is carried out conventionally, often leading to overlapping schedules, information distribution constraints, and low efficiency in monitoring room utilization for both domestic and public events. This investigation objectifies to model and build a website-based room scheduling information system to facilitate the room scheduling mechanism in a more proficient and consolidated layout. The platform development deploys the Waterfall model, which comprises the phases of prerequisite analysis, system design, execution, verification, and maintenance. The application is structured leveraging the Laravel framework alongside a MySQL database and executes the Model View Controller (MVC) pattern. Strategies for gathering information are executed via observation, questions and answers, and literature review. The system validation utilized a User Acceptance Testing (UAT) scheme involving 20 participants consisting of Karanganyar Regency Communications and Information Technology (Diskominfo) employees, students, interns, and general users who had tried the website-based room scheduling information system. The examination findings showed that the system achieved a user approval rating of 89%, categorized as very good. The finalized software is capable of facilitating the progression of managing room usage schedules and provides real-time and structured room availability information for users.